Come to an Enjoyable Class: EFL Extensive Reading - Arwijati Wahjudi (TEFLIN, 2002)
Abstract: This paper argues that an Extensive Reading Class is not a place for reading only, where students read and, therefore, may become better readers. In fact, lots of interaction among students, between student(s) and teacher, can happen, and this happens in an EFL natural situation. The students have something to talk about and are ready to share with the teacher and the other students what they have read. Questions asked are real questions, not comprehension or leading questions. Higher level questions, asking for opinions and feelings, are asked without the students being told to ask these kinds of questions. Students opinions and feelings are expressed simply because they are necessary. Because of its potential as a place where students can exercise somewhat real language with little burden, if any, the writer suggests that Extensive Reading courses be offered at all levels in the English Department, starting from the first year.